Compensation and restitution in investor-state arbitration principles and practice - d (Oxford : Oxford University Press, 2011)
This is a concise guide for lawyers, valuation experts academics, and students of the remedies that foreign investors may seek in international investment disputes. It provides an overview of the legal rules applicable in such circumstances and numerous case studies to show how they are used.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Investments, Foreign (International law); Compensation (Law); Arbitration and award, International